Closing the Gap Between Lookahead and Checkpointing to Provide Hybrid Synchronization - Martello Junior, Edimar Roque; Terra, Acacia; Parizotto, Ricardo; Mello, Braulio (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2020: Anais do XLVII Seminário Integrado de Software e HardwareDO - 10.5753/semish.2020.11321, 2020)
Hybrid synchronization provides more in-depth details about real distributed systems. However, several advances in algorithms to provide synchronization between local processes brings new difficulties to integrate into existing simulation architectures. This paper explores an alternative architecture to provide hybrid synchronization. We present optimistic and conservative synchronization primitives and design mechanisms to enable LPs to cooperate during the execution of a simulation. The results show that our primitives improve the simulation in terms of rollback-time and idleness.